Instagram untuk Negeri: Peran Media Sosial dalam Meningkatkan Akses Informasi Layanan Publik di Kecamatan Sirimau - Riyanti Rahma Tea Said; Ardieansyah Ardieansyah (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
In the digital era, social media has become a strategic tool for enhancing communication between government institutions and the public. Sirimau District, one of the administrative regions in Ambon City, utilizes the Instagram platform to disseminate public service information more quickly, broadly, and efficiently. This study aims to analyze how the official Instagram account of the Sirimau District functions as an information channel and to evaluate its effectiveness and challenges in reaching the community. The research is grounded in the New Public Service theory, which emphasizes citizen participation and information transparency in governance. The findings indicate that Instagram is effectively used to share announcements, service schedules, event documentation, and even facilitate direct interaction with citizens. However, challenges such as digital literacy gaps and limited internet access hinder the platform’s full potential. The study concludes that Instagram plays a significant role in improving transparency and accessibility of public service information in Sirimau District, although additional strategies are needed to ensure inclusive outreach across all community segments.